Intensive home visiting for adolescent mothers in the Family Nurse Partnership in England 2010-2019: a population-based data linkage cohort study using propensity score matching - Ruth Gilbert; Jan van der Meulen; Katie Harron; Eilis Kennedy; Francesca Cavallaro (BMJ Publishing Group, 2024)
Background We evaluated the effectiveness of the Family Nurse Partnership (FNP), an intensive home visiting programme aiming to improve birth outcomes, child health and development, and to promote economic self-sufficiency among teenage mothers.Methods We created a linked cohort of >130 000 mothers aged 13-19 years with live births between April 2010 and March 2019, using administrative data from health (Hospital Episode Statistics), education and children's social care (National Pupil Database). Using propensity score matching, we compared indicators of child maltreatment, health and development outcomes, and maternal hospital utilisation and educational outcomes up to 7 years following birth for mothers who did or did not enrol in FNP.Results We found no evidence of an association between FNP and indicators of child maltreatment, except for an increased rate of unplanned admissions for maltreatment/injury-related diagnoses up to age 2 years for children born to FNP mothers (6.6% vs 5.7%, relative risk (RR) 1.15; 95% CI 1.07, 1.24). There was weak evidence that children born to FNP mothers were more likely to achieve a good level of development at age 5 years (57.5% vs 55.4%, RR 1.05; 95% CI 1.00, 1.09). FNP mothers were less likely to have a subsequent delivery within 18 months of the index birth (8.4% vs 9.3%, RR 0.92; 95% CI 0.88, 0.97).Conclusion Our study supports findings from previous evaluations of FNP showing no evidence of benefit for child maltreatment or health outcomes measured in administrative data. Bias by indication, and variation in the intervention and usual care, may have limited our ability to detect effects. Future evaluations should capture more information on maternal risk factors and additional outcomes relating to maternal/child well-being.